A case of lichen planus pigmentosus that was recalcitrant to topical treatment responding to pigment laser treatment. Issue 5 (2nd May 2014) - Han, Xiuhui Debra; Goh, Chee Leok
Abstract Lichen planus pigmentosus is a rare variant of lichen planus for which no effective treatment is currently available. Patients usually present with hyperpigmented, dark brown macules on sun‐exposed areas or flexural folds. Here we describe a 50‐year‐old Chinese woman who had biopsy‐confirmed lichen planus pigmentosus that was recalcitrant to a variety of topical treatments, but responded to treatment with a pigment laser.